2012
DOI: 10.3382/ps.2012-02275
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome scan for signatures of recent selection reveals loci associated with important traits in White Leghorn chickens

Abstract: Chicken is considered to be an excellent model for genetic studies of phenotypic and genomic evolution, with large effective population size, specialized commercial lines, and strong human-driven selection. High-density chicken SNP chips can help to achieve a better understanding of the selection mechanisms in artificially selected populations. We performed the genome-wide tests for the selection signature in 385 White Leghorn hens and mapped positively selected regions to the genome annotations. Ten QTL relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…The 806 significant core regions (S2 Table) identified in this study was much more than previous report because of the high density SNP chip and genome recombination events [33, 34]. We further compared significant core haplotypes with other haplotypes in these regions and found that the former possess the larger extent of homozygosity than the later.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The 806 significant core regions (S2 Table) identified in this study was much more than previous report because of the high density SNP chip and genome recombination events [33, 34]. We further compared significant core haplotypes with other haplotypes in these regions and found that the former possess the larger extent of homozygosity than the later.…”
Section: Discussionmentioning
confidence: 59%
“…So far, the EHH test has been applied to detect selective signatures of different animals in many researches [13,14,15,16], and proved to be particularly effective among the various statistics [17,18]. Measuring the characteristics of haplotypes, it could identify selection signatures.…”
Section: Introductionmentioning
confidence: 99%
“…Research by Li et al (2012) suggested that genes related to chicken resistance traits are located on chromosome 16, and at the same time, they also located both the egg laying performance and growth performance genes. In our study, the objective genes were LHCGR, ESR2, and DRD2, located on chromosomes 3, 5, and 24, respectively, and our results agree with those of Li et al (2013).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many investigations have used genome-wide association studies (GWAS) to identify special loci used during chicken domestication (van Kaam et al, 1999;Useche et al, 2001;Akey et al, 2002;Reich et al, 2003;Rubin et al, 2010;Gu et al, 2011;Xie et al, 2012;Li et al, 2012Li et al, , 2013. Rubin et al (2010) used whole-genome re-sequencing methods to analyze chicken selection loci and the results revealed that there are 7,000,000 single nucleotide polymorphisms (SNPs), including 1300 deficiency loci, and during chicken domestication specific loci are involved in specialization into broiler (meat-producing) and layer (eggproducing) chicken.…”
Section: Introductionmentioning
confidence: 99%
“…Since natural selection removes variation from the population, and linked sites hitch-hike with the selected variant, signatures of selection should manifest themselves as regions of reduced diversity (Maynard Smith and Haigh 1974). Genome scans have been performed in the chicken to search for domestication sweeps (Wong, Liu et al 2004;Rubin, Zody et al 2010), in domestic populations (Elferink, Megens et al 2012;Li, Liu et al 2012;Zhang, Wang et al 2012;Fan, Ng et al 2013;Gholami, Erbe et al 2014), and in chickens adapted to altitude (Wang, Li et al 2015). These studies have been successful in identifying some plausible candidates.…”
Section: Feralisation and Selective Sweep Mappingmentioning
confidence: 99%